An Astronomical Treatise (Tract. Astron. Hiber.)
This Gaelic manuscript draws on many sources, mainly a Latin translation of an original Arabic work by Mashallah, a Jewish astronomer from Basra in modern day Iraq who flourished just before 800 A.D. The Latin translation by Gerardus Sabionetanus, 'De Scientia Motus Orbis', was printed in Nuremberg in 1504.
The Irish translation has chapter headings in Latin and appears to be incomplete.
Previous location V3.1.38 (This number appears on the spine).
See also Y.4.21.
See enclosures file Z2.2.1(a) which contains transcripts of part of manuscript.
See also Z2.2.21 (English translation).
See also An Irish Astronomical Tract / by Maura Power. London; Irish Texts Society, 1914.
Irish (Old Gaelic) and Latin.
Keywords: Manuscripts, Medieval; Manuscripts, Irish